Farmers and Food Deserts - Budke, Brady; Huntington, Bret; Yu, Han; Joglekar, Shreepad; Hallaq, Tom G. (Kansas State University, 2018)
Kansas farmers produce much of the nation’s crops including wheat, beef, corn and sorghum, yet many of these farmers live more than 10 miles from a grocery store, placing them in food deserts. This story shows how anyone can be a farmer and anyone can provide fresh food for their family through community gardening and farmer’s markets.
Keywords: food deserts; rural food deserts; local farmers; farmers markets